(untitled) (LACCEI, 2024)
Ni1-xCoxFe2O4 (x = 1.0, 0.8, 0.6, and 0.5) nanoparticles were synthesized using the coprecipitation method and subsequent thermal treatment at 800 °C. The structural characterization of the nanoparticles was carried out using X-ray Diffraction, finding that all the compounds presented a single crystalline phase corresponding to the cubic spinel structure. As the concentration of Ni in the compounds increases, a decrease in the lattice parameter was obtained because of the fact that Ni2+ cations are smaller than Co2+. The size, morphology and dispersion of the nanoparticles were analyzed by Transmission Electron Microscopy, finding that the nanocompounds are formed by aggregates of nanoparticles with irregular shapes and mean particle sizes between 34 and 42 nm. The magnetic properties of CoFe2O4 and Co0.5Ni0.5Fe2O4 nanoparticles were studied from magnetization measurements as a function of temperature, in ZFC and FC modes, and magnetization measurements as a function of the applied magnetic field. It was obtained that the nanoparticles are in the blocked magnetic regime in the temperature range from 5 to 320 K. At 5 K, the compounds have large coercive fields of 10683 and 7518 Oe, for CoFe2O4 and Co0.5Ni0.5Fe2O4, respectively. It was found that the values of saturation magnetization, remanent magnetization, and coercive field decrease when replacing Co2+ by Ni2+ in Co ferrite, because the magnetic moments of divalent nickel cations are smaller than those of Co2+ cations.